ANALYSIS OF THE USE OF ENGLISH LOANWORD IN THE CYBER CRIME COLUMN IN KOMPAS DIGITAL NEWSPAPER - Haris Hamdani; Muhammad Zulfadhli; Ferawaty Puspitorini; S.Thoriqul Huda (ETERNAL (English Teaching Journal), 2022)
Language gets the effect of the development in recent era. Some languages receive the development from the other languages such as foreign languages. The loanwords are the words which are adapted from other languages. Many Indonesian words are gained from English. This study was aimed at analyzing and describing the types of English loanwords used in Kompas digital newspaper in the categories of simple word, complex word, and translated word. The researchers used a qualitative descriptive method. The object of this research is the loanword derived from English in the cyber crime column of the Kompas digital newspaper in April and May 2022. The result of the study was that there were 56 English loanwords which were written in Kompas digital newspaper taken from selected columns in April and May 2022. The English loanwords categories analyzed were the simple word, complex word, and translated word. There were 26 English loanwords found as simple word. Then, there were 18 English loanwords found as complex word. Finally, there were 12 English loanwords found as translated word. The simple word of English loanword is the most frequently used in Kompas digital newspaper. Meanwhile, the translated word of English loanword is the least frequent one.